Business & Professional Communication - Kienzler, Donna S. (McGraw-Hill, 2017)
Business depends on communication. People must communicate to plan products and services; hire, train, motive workers; coordinate manufacturing and delivery; persuade customers to buy; and bill them for the sale. Indeed, for many businesses and nonprofit and goverment organizations, thw "product" is information or servicesrather than something tangible. Information and services are created and delivered by communication. In every organization, communication is the way people get work done. Communication take many forms: face to face or phone conversations, tweets, text messaging, social media, and websites. All of these methods are forms of verbal communication, or communication that uses words. Nonverbal comminicaiton does not usr work. Pictures, computer graphics, and company logos are nonverbal. Interpersonal nonverbal signals include how people sit at meetings, how long someone keeps a vistor waiting....